Early infection is an independent risk factor for increased mortality in patients with culture-confirmed infected pancreatic necrosis - Moran, Robert A.; Halloran, Christopher; Guo, Qiang; Umapathy, Chandra; Jalaly, Niloofar Y.; Jain, Saransh; Cowzer, Darren; Cuadrado Robles, Enrique Perez; Quesada-Vázquez, Noé; Szentesi, Andrea; Papp, Mária; Chua, Tiffany; et al. (Pancreatology, 2022)
Background - Mortality in infected pancreatic necrosis (IPN) is dynamic over the course of the disease, with type and timing of interventions as well as persistent organ failure being key determinants. The timing of infection onset and how it pertains to mortality is not well defined. - Objectives - To determine the association between mortality and the development of early IPN. - Methods - International multicenter retrospective cohort study of patients with IPN, confirmed by a positive microbial culture from (peri) pancreatic collections. The association between timing of infection onset, timing of interventions and mortality were assessed using Cox regression analyses. - Results - A total of 743 patients from 19 centers across 3 continents with culture-confirmed IPN from 2000 to 2016 were evaluated, mortality rate was 20.9% (155/734). Early infection was associated with a higher mortality, when early infection occurred within the first 4 weeks from presentation with acute pancreatitis. After adjusting for comorbidity, advanced age, organ failure, enteral nutrition and parenteral nutrition, early infection (≤4 weeks) and early open surgery (≤4 weeks) were associated with increased mortality [HR: 2.45 (95% CI: 1.63-3.67), p < 0.001 and HR: 4.88 (95% CI: 1.70-13.98), p = 0.003, respectively]. There was no association between late open surgery, early or late minimally invasive surgery, early or late percutaneous drainage with mortality (p > 0.05). - Conclusion - Early infection was associated with increased mortality, independent of interventions. Early surgery remains a strong predictor of excess mortality.